2012
DOI: 10.1590/s1808-16572012000200016
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence genes in Escherichia coli strains isolated from diarrheic and healthy feces of dairy calves in Brazil

Abstract: The aim of this work was to test 101 strains of E. coli for virulence factors associated with enterotoxigenic and enterohemorrhagic pathotypes of E. coli isolated from diarrheic and non-diarrheic calves. The virulence factors of E. coli Stx1 (Shiga toxin), Stx2, Ehly (Enterohemolysin), the eae gene, LT-II (heat-labile enterotoxin), STa (heat-stable toxin), and adhesins K99 and F41 were detected by PCR. Serogroups were determined by serological methods and Stx production was observed by biological assays in Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
3
13
1
3
Order By: Relevance
“…Also other study by Moura et al, (2012) showed the frequency of the eae gene was higher in isolates from diarrheic calves 35/58 (60.3%) than in non-diarrheic calves 8/43(18.6%).The gene for Stx1 occurred at high frequencies in the diarrheic strains 24/58 (41.3%) as well as in non-diarrheic 19/43 (44.2%) and all strains that were Stx positive by PCR showed cytotoxicity in Vero cells.…”
Section: Livestock Feces May Contain a Variety Ofmentioning
confidence: 82%
“…Also other study by Moura et al, (2012) showed the frequency of the eae gene was higher in isolates from diarrheic calves 35/58 (60.3%) than in non-diarrheic calves 8/43(18.6%).The gene for Stx1 occurred at high frequencies in the diarrheic strains 24/58 (41.3%) as well as in non-diarrheic 19/43 (44.2%) and all strains that were Stx positive by PCR showed cytotoxicity in Vero cells.…”
Section: Livestock Feces May Contain a Variety Ofmentioning
confidence: 82%
“…In the Southeast region states, the stx1 genotype prevailed in the studies involving beef cattle conducted by Cerqueira et al (), Leomil et al () and Aidar‐Ugrinovich et al (). Regarding dairy cattle, stx1 was the most frequent genotype in studies of Andrade et al (), Moura et al () and Stella et al . ().…”
Section: Virulence Of Stec Isolated From Animalmentioning
confidence: 86%
“…Several studies evaluated the occurrence of STEC in cattle from the São Paulo State (SP), with prevalence ranging from 5·2 to 48·5% (Leomil et al ; Irino et al ; Rigobelo et al ; Aidar‐Ugrinovich et al ; Moura et al ; Stella et al . ).…”
Section: Occurrence Of Stec In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porém os resultados entre os estudos divergem, devido a diversos fatores como a região geográfica estudada, época do ano, número de animais e método de diagnóstico empregado. A frequência de ETEC varia desde zero até 30% (Lage et al 1993, Mendonça et al 1996, Langoni et al 2004, Rigobelo et al 2006, Oliveira Filho et al 2007, Coura 2011, Moura et al 2012, Andrade et al 2012. EPEC varia desde 1,42% até 42,5% (Rigobelo et al 2006, Aidar-Ugrinovoch et al 2007, Coura 2011, Moura et al 2012, Andrade et al 2012 e STEC e EHEC varia entre 2,7% até mais de 50% (Rigobelo et al 2006, Aidar-Ugrinovoch et al 2007, Coura 2011, Andrade et al 2012.…”
Section: Estudos Epidemiológicos Brasilunclassified